A Cutting Re-Mark. Issue 5 (29th September 2020) - Paulden, Tim
Abstract: In mid-August, an algorithm spat out "synthetic" exam grades so absurd and distressing to students that they had to be ditched just four days later. But what exactly went wrong? Dr Tim Paulden explains